2019
DOI: 10.18632/aging.102194
|View full text |Cite|
|
Sign up to set email alerts
|

MiR-27a promotes the autophagy and apoptosis of IL-1β treated-articular chondrocytes in osteoarthritis through PI3K/AKT/mTOR signaling

Abstract: Osteoarthritis (OA) is a common degenerative joint disorder, which involves articular cartilage degeneration as well as joint inflammatory reactions. The recent studies have identified microRNA (miRNA) as one of the epigenetic mechanisms for the regulation of gene expression. Here we aim to reveal the role of miRNA in the regulation of gene expression in articular chondrocytes and its significance in the OA pathogenesis. In the present study, miRNA profiling was performed using OA cartilage and normal healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…Accumulating evidence demonstrated that pro-inflammatory cytokines, such as IL-1β, TNF, and IL-6, are involved in the pathophysiology of OA (Robinson et al, 2016;Philpott et al, 2017;Urban and Little, 2018). Especially, IL-1β can act as an independent pro-inflammatory cytokine alone in promoting the progression of OA by inducing chondrocyte apoptosis and proinflammatory signaling via MAPK, NF-κB, mTOR, and PI3K/Akt signaling pathways (Moon et al, 2018;Cai et al, 2019;Zhou et al, 2019). Several reports have shown that BMSC-derived EVs play an anti-inflammatory role in OA pathophysiology through regulating MAPK, NF-κB, mTOR, and PI3K/Akt signaling pathways (Zhao et al, 2018;Sun et al, 2019;Xia et al, 2019;Zhu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrated that pro-inflammatory cytokines, such as IL-1β, TNF, and IL-6, are involved in the pathophysiology of OA (Robinson et al, 2016;Philpott et al, 2017;Urban and Little, 2018). Especially, IL-1β can act as an independent pro-inflammatory cytokine alone in promoting the progression of OA by inducing chondrocyte apoptosis and proinflammatory signaling via MAPK, NF-κB, mTOR, and PI3K/Akt signaling pathways (Moon et al, 2018;Cai et al, 2019;Zhou et al, 2019). Several reports have shown that BMSC-derived EVs play an anti-inflammatory role in OA pathophysiology through regulating MAPK, NF-κB, mTOR, and PI3K/Akt signaling pathways (Zhao et al, 2018;Sun et al, 2019;Xia et al, 2019;Zhu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the PI3K/AKT/mTOR signaling pathway is one of the classical pathways for autophagy induction. There is increasing evidence showing that the activation of autophagy associated with the inhibition of the PI3K/AKT/mTOR pathway regulates many biological processes, including platelet activation, psoriasis regulation, and osteoarthritis attenuation (Varshney and Saini, 2018;Wang et al, 2018;Cai et al, 2019). However, few studies have focused on the role of autophagy induced by PI3K/AKT/mTOR inhibition in the radioresistance of NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that chondrocyte apoptosis plays a critical role in cartilage degeneration, which is associated with the etiology of OA . Therefore, the anti‐apoptotic role of OLA is must be determined in chondrocytes.…”
Section: Resultsmentioning
confidence: 99%